Minimal alveolar concentration of sevoflurane in combination with remimazolam in adults during laryngeal mask insertion: an up-down sequential allocation study - Yan Huang; HongYu Liao; LinJi Li; Juan Xu; PingPing Jiang; YanXia Guo; KunPeng Liu (BMC Anesthesiology, 2024)
Abstract Background Remimazolam is a novel ultrashort-acting intravenous benzodiazepine sedative-hypnotic. The combination of remimazolam and sevoflurane does not increase respiratory sensitivity, produce bronchospasm, or cause other adverse conditions. We aimed to observe the effects of different remimazolam doses on the minimum alveolar concentration (MAC) of sevoflurane at end-expiration during laryngeal mask insertion and evaluate the effect of sex on the efficacy of the combination of remimazolam on the suppression of laryngeal mask insertion in adult patients. Methods We included 240 patients undergoing laparoscopic surgery under general anesthesia with elective placement of a laryngeal mask (120 males and 120 females). The patients were randomly divided into four groups according to sex: a control group (randomization for female patients, RF0; randomization for male patients, RM0) and three remimazolam groups (RF1, RM1 / RM2, RF2 / RM3, RF3), with 30 patients in each group. Induction was established by vital capacity rapid inhalation induction (VCRII), using 8% sevoflurane and 100% oxygen (6 L/min) in all patients. The (RF1, RM1), (RM2, RF2), and (RM3, RF3) groups were continuously injected with remimazolam at doses of 1, 1.5, and 2.0 mg/kg/h, respectively, while the (RM0, RF0) group was injected with an equal volume of normal saline. The end-expiratory concentration of sevoflurane was adjusted to a preset value after the patient’s eyelash reflex disappeared. After the end-expiratory concentration of sevoflurane was kept stable for at least 15 min, the laryngeal mask was placed, and the patient’s physical response to the mask placement was observed immediately and within 30 s of placement. The MAC of sevoflurane was measured using the up-and-down sequential method of Dixon. Results The calculated MAC of end-expiratory sevoflurane during laryngeal mask insertion in adult females was (2.94 ± 0.18)%, (2.69 ± 0.16)%, (2.32 ± 0.16)% and (1.83 ± 0.15)% in groups RF0, RF1, RF2 and RF3; (2.98 ± 0.18)%, (2.80 ± 0.19)%, (2.54 ± 0.15)% and (2.15 ± 0.15)% in male groups RM0, RM1, RM2 and RM3, respectively. The MAC values were significantly lower in the (RF1-RF3, RM1-RM3) group when compared to the (RF0, RM0) group. There was no significant difference between (RF0, RF1) and (RM0, RM1), but the MAC value of the RF2-RF3 group was significantly lower than that of the RM2-RM3 group. Conclusions Remimazolam can effectively reduce end-expiratory sevoflurane MAC values during laryngeal mask placement in adults. When remimazolam was measured above 1.5 mg/kg/h, the effect of inhibiting laryngeal mask implantation in female patients was stronger than that in male patients. Remimazolam at a dose of 1–2 mg/kg/h combined with sevoflurane induction can be safely and effectively used in these patients.